Management of the Brain: Essential Oils as Promising Neuroinflammation Modulator in Neurodegenerative Diseases - Rosanna Avola; Alessandro Giuseppe Furnari; Adriana Carol Eleonora Graziano; Alessandra Russo; Venera Cardile (MDPI AG, 2024)
Neuroinflammation, a pivotal factor in the pathogenesis of various brain disorders, including neurodegenerative diseases, has become a focal point for therapeutic exploration. This review highlights neuroinflammatory mechanisms that hallmark neurodegenerative diseases and the potential benefits of essential oils in counteracting neuroinflammation and oxidative stress, thereby offering a novel strategy for managing and mitigating the impact of various brain disorders. Essential oils, derived from aromatic plants, have emerged as versatile compounds with a myriad of health benefits. Essential oils exhibit robust antioxidant activity, serving as scavengers of free radicals and contributing to cellular defense against oxidative stress. Furthermore, essential oils showcase anti-inflammatory properties, modulating immune responses and mitigating inflammatory processes implicated in various chronic diseases. The intricate mechanisms by which essential oils and phytomolecules exert their anti-inflammatory and antioxidant effects were explored, shedding light on their multifaceted properties. Notably, we discussed their ability to modulate diverse pathways crucial in maintaining oxidative homeostasis and suppressing inflammatory responses, and their capacity to rescue cognitive deficits observed in preclinical models of neurotoxicity and neurodegenerative diseases.